2019
DOI: 10.1088/1367-2630/ab0781
|View full text |Cite
|
Sign up to set email alerts
|

Can photoemission tomography be useful for small, strongly-interacting adsorbate systems?

Abstract: Molecular orbital tomography, also termed photoemission tomography, which considers the final state as a simple plane wave, has been very successful in describing the photoemisson distribution of large adsorbates on noble metal surfaces. Here, following a suggestion by Bradshaw and Woodruff (2015 New J. Phys. 17 013033), we consider a small and strongly-interacting system, benzene adsorbed on palladium (110), to consider the extent of the problems that can arise with the final state simplification. Our angle-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 63 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…Within this assumption, a PMM can be modeled based on the Fourier transform of a molecular orbital. , Furthermore, if the interactions between the molecules as well as between molecules and substrate are such that the spatial distribution of the wave functions is hardly affected, the orbitals of a free molecule in vacuo are appropriate approximations for the simulations. Previous reports have demonstrated that this premise is reasonably fulfilled in many cases including molecule–substrate systems involving charge transfer and hybridization across the interface and, in particular, even K x PTCDA on Ag(111) . The simulation of experimentally obtained PMMs becomes more difficult if several differently oriented domains are present on the sample.…”
Section: Resultsmentioning
confidence: 94%
“…Within this assumption, a PMM can be modeled based on the Fourier transform of a molecular orbital. , Furthermore, if the interactions between the molecules as well as between molecules and substrate are such that the spatial distribution of the wave functions is hardly affected, the orbitals of a free molecule in vacuo are appropriate approximations for the simulations. Previous reports have demonstrated that this premise is reasonably fulfilled in many cases including molecule–substrate systems involving charge transfer and hybridization across the interface and, in particular, even K x PTCDA on Ag(111) . The simulation of experimentally obtained PMMs becomes more difficult if several differently oriented domains are present on the sample.…”
Section: Resultsmentioning
confidence: 94%
“…The vibrational fine structure of HOMO-peaks allows to assess charge reorganization energies and thus to estimate hopping mobilities by a 'firstprinciple' experiment 279,[333][334][335][336] . Moreover, the development of instrumentation over the last decades has made it possible to measure photoelectron reciprocal-space maps, often termed "orbital tomography", which can be used to reconstruct molecular orbitals in real space and/or to precisely assign photoemission intensities to a particular molecular orbital 286,337115,236,[338][339][340] .…”
Section: Complementary Techniquesmentioning
confidence: 99%
“…The measured angular distribution of photoelectrons is governed by the spatial distribution of electrons in the initial state-the orbital. There is overwhelming evidence that, for  orbitals in conjugated molecules, this relation is a straightforward Fourier transform (24,25). This is valid if the final state of the photoelectron after photoemission can be represented by a plane wave (PW) [so-called plane wave approximation (PWA)].…”
Section: Introductionmentioning
confidence: 99%